2007
DOI: 10.1890/06-1056.1
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton Biodiversity and Lake Trophic State: Explanations Invoking Resource Abundance and Distribution

Abstract: While empirical studies linking biodiversity to local environmental gradients have emphasized the importance of lake trophic status (related to primary productivity), theoretical studies have implicated resource spatial heterogeneity and resource relative ratios as mechanisms behind these biodiversity patterns. To test the feasibility of these mechanisms in natural aquatic systems, the biodiversity of crustacean zooplankton communities along gradients of total phosphorus (TP) as well as the vertical heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(79 citation statements)
references
References 55 publications
5
69
1
3
Order By: Relevance
“…Functional diversity (FD) has been defined as the value and the range of functional traits of the organisms present in a given ecosystem (Diaz and Cabido 2001). The ecological literature about the measurement of functional diversity, which captures how functional trait composition varies among assemblages, has grown during the last decade (i.e., Thompson et al 2005;Barnett and Beisner 2007). Functional diversity can be expressed as the measurement of the branch length of a dendrogram based on similarities between functional traits Gaston 2002, 2009;Cianciaruso et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Functional diversity (FD) has been defined as the value and the range of functional traits of the organisms present in a given ecosystem (Diaz and Cabido 2001). The ecological literature about the measurement of functional diversity, which captures how functional trait composition varies among assemblages, has grown during the last decade (i.e., Thompson et al 2005;Barnett and Beisner 2007). Functional diversity can be expressed as the measurement of the branch length of a dendrogram based on similarities between functional traits Gaston 2002, 2009;Cianciaruso et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is diffi cult to explain this variability because of differences in the lake areas, sampling frequency, and the small numbers of samples collected from each lake (Duggan et al, 2002). Interestingly though, a number of studies have demonstrated a relationship between trophic status (Jeppesen et al, 2000), lake size or area (Dodson, 1992), or phytoplankton spatial heterogeneity (Barnett and Beisner, 2007) and species richness or diversity. Our data suggest a trend towards higher diversity associated with increased macrophyte coverage in LZH, WHL, and NSH than in TXH and BDT.…”
Section: Fig4 Differences In Density (I) Shannon Index (Ii) and Piementioning
confidence: 99%
“…The unimodal productivityzooplankton diversity model (e.g. Dodson et al, 2000;Barnett and Beisner, 2007) suggests that there is an optimum productivity at which zooplankton communities are most diverse. Above this, changes in phytoplankton composition associated with eutrophication lead to the development of zooplankton communities better adapted for dominance by blue-green algae species (Richman and Dodson, 1983;Smith, 1983;Gliwicz and Lampert, 1990;Watson et al, 1997).…”
Section: Correlates Of Zooplankton Species Richness and Compositionmentioning
confidence: 99%
“…Although the precise nature of these effects is debated, the generally accepted models are that richness and composition change unimodally (e.g. Dodson et al, 2000;Barnett and Beisner, 2007) or linearly with productivity (Chase and Ryberg, 2004;Hoffmann and Dodson, 2005), depending on the scale of observation (Chase and Ryberg, 2004) and the metric used to measure productivity (Thackeray, 2007).…”
Section: Introductionmentioning
confidence: 99%